Pengaruh Penggunaan Metode Drill Terhadap Kemampuan Menghitung Keliling dan Luas Bangun Datar - Wardany, Risny Kusuma; Nurlatifah, Nurlatifah; Utami, Ratna Widianti (Sekolah Tinggi Ilmu Agama Islam Putra Galuh Ciamis, 2024)
This research was motivated by the low ability of students in calculating the perimeter and area of data shapes, which may have something to do with the learning methods used by the teacher. To achieve learning objectives, effective learning is needed so that all material presented by the teacher can be mastered by students. This research aims to obtain empirical evidence regarding the use of the drill method to improve students' calculation skills in the topic of perimeter and area of flat shapes. The assessment was carried out in the form of Pre-Experiment with a research design using one group pretest-posttest. The sample in this study was 33 class III students at SDN 1 Gegempalan who were selected purposively. Students' ability to calculate the perimeter and area of flat shapes in mathematics learning before using the drill method, students have the ability to calculate the perimeter and area of flat shapes within the criteria of sufficient and insufficient ability. Students' ability to calculate the circumference and area of figures in mathematics learning after using the drill method shows very good and good abilities. There is an influence of using the drill method on the ability to calculate the perimeter and area of data for students in class III of SDN 1 Gegempalan Cikoneng Ciamis.